Berberine Inhibits Breast Cancer Stem Cells Development and Decreases Inflammation: Involvement of microRNAs and Interleukin-6 - Ibrahim, Nour (Université d'Ottawa | University of Ottawa, 2024)
Background: Breast cancer (BC) is often related to depressive symptoms, influenced by epigenetics. Elevated interleukin-6 (IL-6) levels in BC correlate with inflammation, dysbiosis, cancer stem cells (CSC) stemness, and depression. In cancer chemoprevention, bioactive food components, like berberine (BBR), were shown to target CSCs via microRNAs (miRNA) in vitro and in vivo. This study investigates BBR's impact on breast CSC stemness and depression modulation through IL-6 and epigenetics. Methods: Mammosphere assays and miRNA analysis in murine and human BC cell lines challenged with BBR were used. BBR was orally administered to female Balb/c mice, followed by mammary carcinoma injection. Serum IL-6 and depressive-like behaviors were evaluated, and tumor tissues were collected for ex-vivo assays, miRNA expression, and IL-6 detection. Results: BBR inhibited CSC mammosphere formation and proliferation, upregulated miRNA-Let-7c and miRNA-34a-5p expression in both cell lines. BBR reduced mammosphere formation in breast tumors and increased miRNA-145-5p and miRNA-34a-5p expression, suggesting tumor-suppressive effects. BBR significantly decreased serum IL-6 levels. In the experimental conditions for behavioral studies, BBR did not have any effect on depressive-like behaviors. Conclusion: This study highlights BBR’s potential as an "Epi-Natural Compound" for BC prevention and inflammation reduction.
Keywords: Breast Cancer; Berberine; Epigenetics; microRNA; Cancer Stem Cells